Вещно-правовые способы защиты права собственности в Российской Федерации - Ryskina, Kseniya (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2014)
The aim of the study is to evaluate the property rights protection system in the civil law system of the Russian Federation. The author present the law instruments that owner and possessor are entitled to.
Property rights protection system in the Russian Federation
Keywords: protection of property rights; owner; possessor; civil law